EFEKTIVITAS KEBIJAKAN PERLINDUNGAN ANAK DARI TINDAK KEKERASAN DI DP3A KOTA SEMARANG (Studi kasus di SMP Negeri 32 dan SMP Negeri 36 Semarang) - Findyona Putri, Kanaya; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2025)
Semarang City is facing an increase in cases of violence against children, despite the enactment of Regional Regulation Number 5 of 2016 concerning the Protection of Women and Children. This policy is implemented by the Semarang City DP3A (Women's Empowerment and Child Protection Service) to protect children from violence. This study aims to determine the effectiveness of child protection policies, as well as to identify phenomena that influence them. The study used a descriptive qualitative method with analysis based on five phenomena of policy effectiveness according to Riant Nugroho, namely appropriate policy, implementer, target, environment, and process. The results of the study indicate that child protection policies in Semarang City have been implemented and show optimality in the phenomena of appropriate policy and appropriate target. However, the phenomena of appropriate implementer, appropriate environment, and appropriate process still have room for improvement. Supporting phenomena include effective communication, policy implementer disposition, and an organized bureaucratic structure. The inhibiting phenomena are limited internal training, and minimal budget available. Recommendations include community-based socialization strategies, increasing the involvement of the Women and Children Protection Network (JPPA), and developing internal training.